Apprenticeship in England : the continued role of the academic-vocational divide in shaping learner identities - Brockmann, Michaela [Verfasser]; Laurie, Ian [Verfasser] (My University, 2016)
"Successive governments have pledged to enhance the quality of apprenticeship in Britain so as to achieve 'parity of esteem' with academic study. Yet, at the same time, the discourse of the academic-vocational divide has dominated the academic, policy-maker and practitioner debates. This paper draws on two recent studies designed to explore the learner identities of apprentices on different apprenticeship programmes: motor vehicle maintenance (level 2) and engineering (level 3). Through this work, we are able to explore the role of the academic-vocational divide in identity construction and to challenge assumptions about vocational learners. It will be argued, that, far from being 'naturally practical', the young people draw on normative discursive categories in their construction of continuous identities. The findings raise important questions about the UK apprenticeship system as currently conceived, while at the same time drawing attention to the possibility for change." (Autorenreferat; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; P 2.3 Auszubildende; I 2.2.1 Westeuropa; Berufsausbildung; Auszubildender; Kraftfahrzeuggewerbe; Maschinenbau; Identitätsbildung; Vereinigtes Königreich